Nursing education: a case study of a Bachelor of Science Nursing programme in Abu Dhabi, United Arab Emirates. - WOLLIN, JUDY A.; FAIRWEATHER, CARRIE T. (Journal of Nursing Management, 2012)
wollin j.a. & fairweather c.t. (2012) Journal of Nursing Management 20, 20-27 Nursing education: a case study of a Bachelor of Science Nursing programme in Abu Dhabi, United Arab Emirates Aim The aim of the present study was to report the process and outcomes of a collaborative venture to offer a Bachelor of Science Nursing programme in Abu Dhabi. Background An international educational collaboration between the Abu Dhabi government in the United Arab Emirates (UAE) and Griffith University (GU) Australia, successfully established a College of Health Sciences offering a Bachelor of Science Nursing (pre- and post-registration). Methods The report was written to reflect the chronological order of events as the Bachelor of Science Nursing programme was rolled out in Abu Dhabi commencing in 2007. Results The results of this initiative included the successful delivery of the programme and the gaining of initial accreditation in Abu Dhabi. Conclusion The paper presents important insights into the collaborative nature of the agreement and the unique outcomes; dual awards from UAE and Australia. Implications for nursing management The success of this initiative required ongoing commitment from the collaborating partners. The programme required ongoing support from the School of Nursing and Midwifery in Australia. Griffith University provided the Head of School and Deputy Head of School for Abu Dhabi and the curriculum. The academic and administrative support from Australia was significant and must be incorporated into any business plan when planning such a venture.